PENGARUH IMPLEMENTASI AI PADA SISTEM INFORMASI MANAJEMEN PENJUALAN - Simbolon, Mangantar; Darwis Manalu (CV. KAMPUS AKADEMIK PUBLISING, 2026)
The development of Artificial Intelligence (AI) technology is driving the transformation of management information systems, including sales management information systems. This study aims to analyze the influence of AI implementation on the effectiveness of sales management information systems based on a review of scientific literature. The research method employed is a qualitative approach with a literature study, utilizing secondary data sources in the form of national and international journals discussing the application of AI in information systems and sales management. The analysis was conducted through the process of grouping, comparing, and synthesizing findings from previous studies. The results of the review indicate that AI implementation has a positive influence on the effectiveness of sales management information systems, particularly in improving information quality, data processing speed, and the accuracy of managerial decision-making. AI enables sales information systems to generate real-time and predictive information through the utilization of data analytics, demand forecasting, and customer behavior analysis. However, the effectiveness of AI implementation is contextual and highly influenced by organizational readiness, including the quality and availability of data, technological infrastructure, and human resource competence. Without the support of these factors, AI implementation has the potential not to provide optimal added value. This study confirms that AI is not merely an operational automation tool, but a strategic component in sales management information systems that can enhance organizational competitiveness if implemented in a planned manner and aligned with business needs.